Dr Miller and the islanders - Whitehead, Jessica; Thomas, Damon ([S.l.] : A Uden Associates [production company] ; Bristol : BBC Education and Training [distributor], 1995)
Story about the experience of Dr Miller in Thursday Island. Described the people of Thusrday Island in Australia. Explain the social life and customs of the islanders.
Copy available in DVD format
Editors, Zam Baring, Adam De Wan ; series editor, John Lynch
Keywords: Islands -- Australia; Thursday Island (Qld) -- Social life and customs; Thursday Island (Qld) -- Social conditions